SMART TEACHING MELALUI WORKSHOP INOVASI PEMBELAJARAN DENGAN TEKNOLOGI DAN APLIKASI DIGITAL - Rizan, Okkita; Irawadi, Syafrul; Perkasa, Eza Budi; Supardi, Supardi; Hamidah, Hamidah (ISB Atma Luhur, 2025)
The digital era demands that teachers possess ICT competencies and a high level of professionalism in designing and implementing learning activities that are relevant to the needs of the 21st century. The concept of smart teaching has emerged as one of the approaches to address these demands, through the use of technology and digital applications to create interactive, adaptive, and meaningful learning experiences. However, the education system in Indonesia still faces several challenges. Teachers’ digital literacy remains uneven, and many still rely on conventional teaching methods. As a result, the use of technology in learning has not been optimized, and teachers’ professionalism has yet to develop in line with the requirements of the digital era. Workshops on technology-based learning innovation can serve as a strategic solution to these issues. Through such workshops, teachers can gain practical skills in using learning applications and digital tools. In addition, workshops provide a platform for sharing experiences and building professional networks, thereby fostering collaborative innovation in teaching practices. This approach not only enhances digital literacy but also strengthens teachers’ pedagogical, social, and professional competencies in a sustainable manner. With a workshop design that is practical, contextual, and needs-oriented, smart teaching can be effectively realized. Improving teachers’ competence and professionalism through workshops is expected to enhance the quality of learning, reduce the gap in technology utilization in schools, and support Indonesia’s educational transformation toward an adaptive, inclusive, and globally competitive system